Tuberculous mastoiditis in children - K. U. Mugiyo; N. N. Rahayoe; H. H. Hendarto (Paediatrica Indonesiana, 1981)
The authors emphasized that though up till now such cases are still unfrequently encountered one should always be aware that tuberculous mastoiditis in infants and young children has quite high prevalence.